Tinjauan Yuridis tentang Rechtvinding (Pemenuhan Hukum) dalam Hukum Perdata Indonesia - K Martam, Nurmin (Gorontalo Law Review, 2018)
The law has a function to provide protection to human interests (all human beings without exception). Therefore, the law must be implemented so that human interest can be protected. In practice, the law may proceed normally and peacefully, but there may also be legal violations in practice. In this case the law that has been violated must be enforced. It is through law enforcement that this law becomes a reality. In upholding the law there are three elements that must always be considered: legal certainty (Rechtssicherheit), usefulness (Zweckmassigkeit) and justice (Gerechtigkeit).In the life of society required a legal system to create a harmonious and orderly society life. In fact the law or legislation that is made does not cover all cases that arise in society, making it difficult for law enforcement to complete the case. In the scope of positive law in Indonesia, the principle "that judges should not refuse a case", contained in article 10 paragraph (1) of Law no. 44 Year 2009 on Judicial Power.Constitutional judges and judges are required to explore, follow, and understand the legal values and sense of justice living in society. This is the basis that it is unavoidable that the rechtsvinding process should still be done by the judge in deciding cases not found clearly and firmly in legislation.The approach used in this study is a normative juridical approach, namely by using the theories and opinions of scholars by conducting an analysis of the provisions applicable in positive law of Indonesia.In line with the increasingly dynamic society, it demands a dynamic legal development as well. This is in line with the civil law system itself that is dynamic and not static. The important task of the judge, therefore, is to adapt the law to concrete events in society. If the law can not be judged appropriately according to the words of the law or the law is unclear, then the judge must interpret the law, so that the judge can make a truly fair law decision in accordance with what Which is the purpose and objective of the law, namely the achievement of legal certainty.